Performance of Broiler Fed on Commercial Ration Containing Banana Tuber Meals - Aswandi Aswandi (Jurnal Ilmu dan Teknologi Peternakan, 2016)
Feedstuff availability is one of the problems in the poultry meat production system, which uses corn as the main energy source in the ration. One of the alternative solutions is to identify the feedstuff that has potential, qualitative and quantitative, to substitute it. Banana tuber contains high carbohydrate and low fiber components so that it can be used as energy source in the ration. The aim of research was to compare the benefit between the ration containing banana tuber meals, which was provided from batu and kapok banana tuber, and the commercial broiler ration. One hundred and ninety two of broiler chicks were raised for 30 days and were randomly allotted to one of four treatment diets according to completely randomized design with four replications for each treatment. The experimental rations were P0 (control, 100%of commercial feed), P1 (60% of commercial feed + 30% of banana tuber meal + 10% fish meal), P2 (70% of commercial feed + 20% of banana tuber meal + 10% fish meal), and P3 (80% of commercial feed + 10% of banana tuber meal + 10% fish meal).The results of the study indicated that the average body weight gain was 58.75, 54.65, 51.95, and 48.68 g/d for the treatment P0, P1, P2, and P3, respectively. In conclusion, the use of 30% banana tuber meals in the commercial feed mixtures does not deteriorate the performance (daily gain) of the broiler.